KONTESTASI FRAMING MEDIA ONLINE INDONESIA MODEL ROBERT M. ENTMAN TERHADAP PROGRAM BARAK MILITER DEDI MULYADI - Endy Setyawan; Ahmad Zaini; Wahid Mubarodin; Asri Aulia; Muhammad Ikhwanul Reza; Malik Ibrahim (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze how online media frame the Military Barrack Program initiated by West Java Governor Dedi Mulyadi as a response to rising juvenile delinquency. Employing a qualitative approach and Robert Entman’s framing analysis model, the research examines four key elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The data were collected from online news articles published by four major national media outlets Tempo.co, Detik.com, Kompas.com, and CNNIndonesia.com between January and June 2025. The findings indicate that most media outlets frame the program positively, emphasizing character-building and discipline, portraying military intervention as a legitimate solution to youth behavioral problems. Criticism regarding child rights violations and psychological impacts appears only as marginal counter-narratives and does not dominate the overall discourse. Media framing plays a significant role in shaping public perception and legitimizing this controversial policy. This study contributes to media studies, local politics, and public policy discourse, and recommends expanding the scope to include local and alternative media through mixed-methods approaches for a more comprehensive understanding.